Probiotic potential of Lactobacillus paracasei FM-LP-4 isolated from Xinjiang camel milk yoghurt. (November 2016) - Wang, Ying; Zhou, Jianzhong; Xia, Xiudong; Zhao, Yancun; Shao, Weilan
Abstract: Fifty three probiotic lactic acid bacteria (LAB) strains with high anti-oxidative activity from Xinjiang camel milk yoghurt were screened and identified. Four strains showed higher 2, 2-diphenyl-1-picrylhydrazyl scavenging activity and reducing power than the reference strain Lactobacillus rhamnosus GG (ATCC53103) with strain FM-LP-4, identified as Lactobacillus paracasei by 16S rDNA nucleotide sequencing, showing the highest. Strain FM-LP-4 also showed higher stress tolerance properties (acidity, bile, and osmotic pressure) and adhesion properties than L. rhamnosus GG. The in vivo antioxidant activity of FM-LP-4 was further assayed ind -galactose-induced oxidative damaged mice. Administration of FM-LP-4 significantly enhanced the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), and inhibited the biosynthesis of malondialdehyde (MDA) and protein carbonyl in a dose-dependent manner. Additionally, FM-LP-4 strain could significantly decrease the endotoxin level in the serum of mice. Overall, strain FM-LP-4 is a promising probiotic candidate for preparations of functional foods and antioxidant supplements.